An Analysis of the English Club to Support Students’ Speaking Performance at Junior High School - Rizka Aulia; Fatimatuz Zahra; Muhammad Anwarul Fadli; Win Listyaningrum Arifin; Sheila Najwa (Indonesian TESOL Journal, 2025)
This study discusses how the English Club supports students' speaking performance at SMP Negeri 1 Salatiga. Several previous studies have shown that English Clubs can improve fluency and confidence, but few studies have discussed how club activities are carried out and how clubs support the improvement of students' speaking performance at the junior high school level. This study aims to fill this gap by describing the implementation of the English Club and the forms of support provided to students. The study uses a descriptive qualitative method through observation and semi-structured interviews with eight members and two facilitators of English Club. The results show that activities such as discussions, interactive games, paired conversations, and role-plays improve students' fluency, vocabulary, pronunciation, and confidence. The relaxed and supportive environment reduces anxiety and encourages active participation. This study confirms that English clubs are an effective platform for developing students' speaking performance and provides practical implications for schools and teachers in designing more structured and meaningful club activities.